Effects of Vitamin D Levels on Quality of Life in Osteoporosis - Original Investigation - İlker Coşkun Benlidayı; Füsun Güler Uysal; Sibel Başaran; Rengin Güzel (Türk Osteoporoz Dergisi)
Vitamin D deficiency causes muscle weakness, impairs bone formation and neuromuscular coordination, thus increases fracture risk. It is well known that pain and functional disability caused by fractures impairs quality of life (QOL). However, studies investigating the association between vitamin D deficiency and QOL are insufficient. This study investigates the effects of vitamin D level on QOL in osteoporotic patients. 286 patients (mean age 60.51±9.1 years) with postmenapousal, senile or male osteoporosis were included in the study. Demographic data, physical activity level and back pain were recorded. Bone turnover markers, 25(OH)vitaminD, PTH levels and bone mineral density (BMD) were evaluated. Spinal deformity index (SDI) was calculated by lateral thoracolomber X-rays. QOL was assessed using QOL Questionnaire of the European Foundation for Osteoporosis (QUALEFFO). 25(OH)vitaminD levels below 12ng/ml was accepted as vitamin D deficiency. 25(OH)vitaminD level of the patients was 23.19±13.1ng/ml and 34 were (11.8%) vitamin D deficient. 25(OH)vitaminD levels were not correlated with age, body mass index, concomitant diseases, postmenopausal years, risk factors, pain, and dietary calcium intake. There was also no correlation between 25(OH)vitaminD and bone turnover markers, SDI and BMD. 25(OH)vitaminD was correlated with physical activity level (p=0.001 and r=0.198) and physical, social, mental function subscales and total score of QUALEFFO. In vitamin D deficient group physical and social function subscales and total QUALEFFO scores were more impaired (p=0.001, p=0.004, p=0.003 respectively). Vitamin D deficiency negatively effects physical and social functions of osteoporotic patients and impairs their QOL. (Osteoporoz Dünyasından 2006; 12 (2): 35-38)